Rāshṭrapati Rājendra Prasāda : saṃsmaraṇa aura jīvana-darśana - Sahāya, Śivapūjana, 1893-1963 (SAMP early 20th-century Indian books project ;, 1949)
Collection of essays on Rajendra Prasad, 1884-1963, former president of India.